Dynamic Modeling and Simulation Analysis of Herringbone Gear Transmission System - Lulu Qian; Peng Lou; Jin Feng; Zhongtao Huang; Jian Luo (Jixie chuandong)
A herringbone gear transmission system is taken as the research object. A method of gear system-level modeling and simulation analysis is proposed. Based on the finite element node method，a dynamic model considering rigid rotor-shaft-bearing and the meshing of gears is established. Then the resonance speed of the system is analyzed and the result is compared with the experimental data to verify the reliability and limitations of the finite element node model. Then a 3D finite element model used for natural frequency calculation and vibration mode analysis is established. The modeling of gear meshing is used in finite element node method. Finally，combined with the modal analysis and response analysis，the theoretical analysis is compared with the experimental data. And the cause of experimental resonance is determined and resonance localization is realized，which provides direction for decreasing the vibration amplitude and avoiding the vibration.